Research and Development as the Foundation for PAI Curriculum Innovation - Rogibah; Ahmad Abdul Rochim (Jurnal Ilmu Pendidikan, 2026)
Islamic Education (PAI) plays a crucial role in shaping students' character, morals, and spirituality. However, the PAI curriculum is often considered inadequate in addressing the evolving needs of modern times. To address this challenge, research and development (R&D) is a critical approach for creating a more adaptive, contextual, and innovative curriculum. This article discusses the importance of R&D in the innovation of the PAI curriculum, focusing on the role of research in uncovering various issues in the practice of teaching, such as the lack of connection between the material and real-life situations, as well as weaknesses in interactive teaching methods. Through a research-based approach, it is expected that the PAI curriculum can be developed to be more functional and transformative, in line with the times and the needs of students. Additionally, this article explores the benefits, challenges, and obstacles faced in the application of R&D in the PAI curriculum, as well as the R&D models that can be used for curriculum development. In conclusion, strong research can ensure that the innovation of the PAI curriculum effectively contributes to improving the quality of Islamic education and the development of students' character.